Survival according to the site of metastasis in triple-negative breast cancer patients: The Peruvian experience - Piedra-Delgado, L (2024)
Background Evidence regarding differences in survival associated with the site of metastasis in triplenegative breast cancer (TNBC) remains limited. Our aim was to analyze the overall survival (OS), distant relapse free survival (DRFS), and survival since the diagnosis of the relapse (MS), according to the side of metastasis. Methods This was a retrospective study of TNBC patients with distant metastases at the Instituto Nacional de Enfermedades Neoplasicas (Lima, Peru) from 2000 to 2014. Prognostic factors were determined by multivariate Cox regression analysis. Results In total, 309 patients were included. Regarding the type of metastasis, visceral metastasis accounted for 41% and the lung was the most frequent first site of metastasis (33.3%). With a median follow-up of 10.2 years, the 5-year DRFS and OS were 10% and 26%, respectively. N staging (N2-N3 vs. N0, HR = 1.49, 95%CI: 1.04-2.14), metastasis in visceral sites (vs. bone; HR = 1.55, 95%CI: 0.94-2.56), the central nervous system (vs. bone; HR = 1.88, 95% CI: 1.10-3.22), and multiple sites (vs. bone; HR = 2.55, 95%CI:1.53-4.25) were prognostic factors of OS whereas multiple metastasis (HR = 2.30, 95% CI: 1.42-3.72) was a predictor of MS. In terms of DRFS, there were no differences according to metastasis type or solid organ. Conclusion TNBC patients with multiple metastasis and CNS metastasis have an increased risk of death compared to those with bone metastasis in terms of OS and MS.